Safety assessment of the process KREYENBORG IR Clean+ (universal) used to recycle post‐consumer PET into food contact materials - EFSA Panel on Food Contact Materials (FCM); Claude Lambré; Riccardo Crebelli; Maria daSilva; Koni Grob; Maria Rosaria Milana; Marja Pronk; Gilles Rivière; Mario Ščetar; Georgios Theodoridis; Els Van Hoeck; Nadia Waegeneers; et al. (EFSA Journal, 2025)
Abstract The EFSA Panel on Food Contact Materials (FCM) assessed the safety of the recycling process KREYENBORG IR Clean+ (universal) (EU register number RECYC329). The input is hot washed and dried poly(ethylene terephthalate) (PET) flakes mainly originating from collected post‐consumer PET containers, with no more than 5% PET from non‐food consumer applications. The flakes are heated in a continuous infrared (IR) dryer (step 2) before being processed in a finisher reactor (step 3). Having examined the challenge test provided, the Panel concluded that both steps are critical in determining the decontamination efficiency of the process. The operating parameters to control the efficiency of these critical steps are temperature, air/PET ratio and residence time. It was demonstrated that this recycling process ensures that the level of migration of potential unknown contaminants into food is below the conservatively modelled migration of 0.0481 or 0.0962 μg/kg food, depending on the molar mass of a contaminant substance. Therefore, the Panel concluded that the recycled PET obtained from this process is not of safety concern, when used at up to 100% for the manufacture of materials and articles for contact with all types of foodstuffs, including drinking water, for long‐term storage at room temperature or below, with or without hot‐fill. Articles made of this recycled PET are not intended to be used in microwave and conventional ovens and such uses are not covered by this evaluation.